Mobile Phone Preferences Segmentation Using The K-Means Clustering in Indonesia - Annisa Nurwanda Putri; Pratiwi, Pratiwi; Putri Syifa Humaira; Jerry Heikal (CV. ULIL ALBAB CORP, 2025)
This study investigates consumer preferences for mobile phones in Indonesia using the K- Means Clustering method. Data from 114 respondents were analyzed to identify key characteristics and preferences, focusing on variables such as age, gender, income, brand, and features like storage, connectivity, design, and accessories. The results revealed six distinct clusters, each representing unique consumer segments, such as Tech-Savvy Seekers, Secure Tech Enthusiasts, Performance Prioritizers, Security-Centric Pragmatists, Style-Savvy Connectors, and Endurance Seekers. The segmentation process highlights significant differences in consumer behavior, with some clusters emphasizing high performance and advanced connectivity features, while others prioritize affordability, security, and design. Based on the STP (Segmentation, Targeting, Positioning) framework, two target segments were identified: Tech-Savvy Seekers and Endurance Seekers. These segments were selected due to their high purchasing power and strong demand for premium mobile phone features, including long battery life and powerful performance. The proposed value proposition for these target segments is